An update on dietary consideration in inflammatory bowel disease: anthocyanins and more. (3rd October 2018) - Farzaei, Mohammad Hosein; El-Senduny, Fardous F.; Momtaz, Saeideh; Parvizi, Fatemeh; Iranpanah, Amin; Tewari, Devesh; Naseri, Rozita; Abdolghaffari, Amir Hossein; Rezaei, Nima
ABSTRACT: Introduction : Inflammatory bowel disease (IBD) is a chronic idiopathic inflammatory disorder. A wealth of data pointed out that various aspects of chronic inflammation may be affected by several specific dietary factors. This paper calls attention to anthocyanins enriched plant food and anthocyanin dietary supplements, whose role in the management of IBD and its associated oncogenesis deems crucial. Area covered : We updated the most relevant dietary anthocyanins with potential anti-colitis and preventive effect on inflammatory associated colorectal cancer based on the recent animal and human researches along with revealing the major cellular and molecular mechanisms of action. Mounting evidence reported that anthocyanins enriched plant foods perform their protective role on IBD and inflammatory-induced colorectal cancer via different cellular transduction signaling pathways, including inflammatory transcription factors, SAPK/JNK and p38 MAPK cascade, JAK/STAT signaling, NF-kB/pERK/MAPK, Wnt signaling pathway, Nrf2 cytoprotective pathway as well as AMPK pathway and autophagy. Expert commentary : Combination of anthocyanins enriched dietary supplements with existing medications can provide new therapeutic options for IBD patients. Further, well-designed randomized control trials (RCTs) are essential to evaluate the role of anthocyanins enriched medicinal foods as well as isolated anthocyanin components as promising preventive and therapeutic dietary agents for IBD and its associated oncogenesis.